Incrementing effect on cold water solubility, structural and functional properties of alcohol-alkali treated Plectranthus rotundifolius starch by organic acids - Plachikkattu Parambil Akhila; Kappat Valiyapeediyekkal Sunooj; Ganesh Revathi; Basheer Aaliya; Muhammed Navaf; Cherakkathodi Sudheesh; Sarasan Sabu; Abhilash Sasidharan; Deep Narayan Yadav; Shabir Ahmad Mir; Johnsy George; Maximilian Lackner (Applied Food Research, 2022)
In this study, three organic acids (citric, lactic, and acetic acid) were pretreated separately on P. rotundifolius starch, and their effects on the structural, functional, and rheological properties of cold water soluble (CWS) starches were investigated. In comparison to native starch, all the modified samples showed granular swelling, and acid pretreatment led to degradation and leaching of the granules. In FT-IR spectra, a peak at 1724 cm−1 confirmed the esterification of organic acids. All the modified starches lost their A-type diffraction pattern and showed a significant (p ≤ 0.05) decrease in the relative crystallinity. HPG showed a significantly higher cold water swelling power than native (2.13 g/g) starch, and lactic acid pretreatment enhanced the cold water swelling power to 9.91 g/g. Citric acid esterified CWS showed a significant increase in cold water solubility (63.1%) and freeze-thaw stability. Thus, this study found that each organic acid treatment affected CWS P. rotundifolius starch differently and has potential application in a refrigerated, instant, or frozen food products.